A local redox cycling-based electrochemical chip device with nanocavities for multi-electrochemical evaluation of embryoid bodies. Issue 23 (20th October 2015) - Kanno, Yusuke; Ino, Kosuke; Shiku, Hitoshi; Matsue, Tomokazu
Abstract : We developed a local redox cycling-based electrochemical (LRC-EC) device with nanocavities for multi-electrochemical detection of cell activity. Abstract : An electrochemical device, which consists of electrode arrays, nanocavities, and microwells, was developed for multi-electrochemical detection with high sensitivity. A local redox cycling-based electrochemical (LRC-EC) system was used for multi-electrochemical detection and signal amplification. The LRC-EC system consists of n 2 sensors with only 2 n bonding pads for external connection. The nanocavities fabricated in the sensor microwells enable significant improvement of the signal amplification compared with the previous devices we have developed. The present device was successfully applied for evaluation of embryoid bodies (EBs) from embryonic stem (ES) cells via electrochemical measurements of alkaline phosphatase (ALP) activity in the EBs. In addition, the EBs were successfully trapped in the sensor microwells of the device using dielectrophoresis (DEP) manipulation, which led to high-throughput cell analysis. This device is considered to be useful for multi-electrochemical detection and imaging for bioassays including cell analysis.